Original paperEvaluation of clinico-epidemiological and histopathological features of pityriasis rosea - Özyürek, Gaye Devrim; Alan, Sevil; Çenesizoğlu, Erol (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: Pityriasis rosea is a sudden-onset and self limiting disease with specific skin rash. The exact etiology is still not clear. Aim : To determine epidemiological, etiological, clinical and histopathological features in pityriasis rosea (PR). Material and methods : Fifty two patients (older than 18 years) with PR were included in this study. Patients were examined for epidemiological and etiological features. Biopsy specimens obtained from secondary eruptions were histopathologically evaluated with hematoxylin-eosine and immunohistochemically evaluated with CD3 and CD20 monoclonal antibodies. Results: Age range of patients was 18–53, mean age was 29.3 ±9.5 and women-to-men ratio was 1.08/1. Thirty-nine (75%) patients had a history of wearing new clothes, 27 (51.9%) patients had a history of recent respiratory tract infection, 15 (28.8%) patients had a history of recent gastrointestinal infection. Eczematous changes were detected in biopsy materials by histopathological evaluation, and cellular infiltrate was positively stained with pan T-cell marker CD3 and negatively stained with B lymphocyte marker CD20 in all biopsy materials in immunohistochemical examination. Conclusions : In our study, frequency of pre-disease infection and prodromal symptoms history were determined to be higher than the results of similar studies in the literature. These higher results suggest that PR may be delayed-type hypersensitivity to an infectious factor. However, positive staining of all biopsy materials with pan T lymphocyte marker CD3 supports the association with cellular immunity. We believe that more extensive studies are needed on this issue.